Distribusi Data Tahunan Menjadi Data Bulanan - Wahyuni, Sri Eko (MEDIA KOMUNIKASI TEKNIK SIPIL, 2005)
InÂ  the process of planning, design and management of water resources system, a long term data on hydrology is needed in order to obtain good analysis and final result. In Indonesia, usually it is very difficult to get a complete and appropriate data on hydrology at certain locations. To cope with the constrains and lack of data on hydrology as is mentioned above, experts on hydrology tend to solve the problems with the following methods: Stochastic analysis, Correlation and regressions analysis, and Simulation analysis on the watershed. In this paper, the phenomenon of the distribution of annual rainfall to monthly rainfall will be discussed utilizing stochastic analysis (i.e. temporal disagregation model), by presserving their statistical characteristics. The output of this model, which is quite reliable and can be use, among other, as a sound base for development of water resources and flood control.Permalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3926[How to cite: Wahyuni, S.E., 2005, Distribusi Data Tahunan Menjadi Data Bulanan, Jurnal Media Komunikasi Teknik Sipil, Volume 13, Nomor 3, pp. 106-116]